Evaluation of Inhaled Insulin Therapy for Diabetes Mellitus - Siddiqui, NI (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2):237-45 The abstract of this article is available on the PubMed website